Safe in the Rooms of A.A.: How Anonymity Helps Reduce the Stigma of Help-seeking and Reinforces Solidarity and Group Cohesiveness. Issue 1 (2nd January 2020) - Ippolito, Tracy A.
ABSTRACT: Initially embraced as a protective measure, anonymity is now a cornerstone of Alcoholics Anonymous (A.A.) for reasons far beyond member confidentiality. This manuscript considers how today's A.A. members understand and internalize the tradition of anonymity. The study: (1) explores how anonymity is defined and practiced by contemporary A.A. members; (2) examines whether the perception of anonymity in A.A. plays a role in help-seeking behaviors; and (3) investigates member understandings of the "spiritual nature" of anonymity.